1996
DOI: 10.1002/(sici)1097-0061(19960615)12:7<653::aid-yea953>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the repeated UASINO element in the promoters of the INO1 and CHO2 genes of yeast

Abstract: In yeast, INO1 and CHO2 gene expression is subject to repression in response to inositol and choline supplementation. The response by both genes to inositol is controlled by a single set of regulatory factors and the highly conserved and repeated UASINO element (consensus: 5′ CATGTGAAAT 3′) that is found in multiple copies in both promoters. However, none of the native elements found in the INO1 and CHO2 promoters constitutes an exact match to the consensus element and the functionality of individual elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
(14 reference statements)
3
21
0
Order By: Relevance
“…Several genes involved in fatty acid and sterol biosynthesis as well as inositol transport have been reported as containing putative UAS INO elements in their promoters (Greenberg and Lopes, 1996). Functional analyses of many of these genes confirm a role for Ino2p and/or UAS INO in their activation (Chirala et al, 1994;Koipally et al, 1996;Grauslund et al, 1999). Our microarray analysis of p180-expressing strains revealed several upregulated genes whose promoters contain known of putative UAS INO elements including INO1, GUT1, and SCS3 (unpublished results).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several genes involved in fatty acid and sterol biosynthesis as well as inositol transport have been reported as containing putative UAS INO elements in their promoters (Greenberg and Lopes, 1996). Functional analyses of many of these genes confirm a role for Ino2p and/or UAS INO in their activation (Chirala et al, 1994;Koipally et al, 1996;Grauslund et al, 1999). Our microarray analysis of p180-expressing strains revealed several upregulated genes whose promoters contain known of putative UAS INO elements including INO1, GUT1, and SCS3 (unpublished results).…”
Section: Discussionsupporting
confidence: 52%
“…When inositol and choline levels are low, a transcription factor complex composed of the basic helix-loop-helix (bHLH) proteins, Ino2p and Ino4p, activates the expression of many genes encoding phospholipid, fatty acid, and sterol biosynthetic enzymes. Ino2p and Ino4p form a functional heterodimer that binds to a conserved upstream activating sequence (UAS INO ) residing in the promoters of these genes (Lopes et al, 1991;Ambroziak and Henry, 1994;Nikoloff and Henry, 1994;Koipally et al, 1996). Ino2p has been shown to contain transactivation domains (Schwank et al, 1995), whereas Ino4p is required for the binding of the complex to UAS INO .…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of a requirement for increased lipid biosynthesis comes from published studies in yeast which demonstrated that p180-induced membrane biogenesis fails to occur in cells lacking the INO2 gene, a master regulator of lipid biosynthesis . Virtually all of the lipid biosynthetic gene sequences that have been examined have INO2 regulatory elements in their promoter sequences (Lopes and Henry 1991;Nikoloff et al, 1992;Ambroziak and Henry, 1994;Nikoloff and Henry, 1994;Koipally et al, 1996). This group includes a multitude of enzymes and transporters involved in lipid and sterol metabolism (Greenberg and Lopes, 1996;Henry and PattonVogt, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In their presence, transcription is repressed and in their absence, it is activated. This regulation is controlled by the cis-acting promoter element UAS INO [9,10], which is the binding site for the heterodimeric transcriptional activator, Ino2p/Ino4p [11,12]. Despite the constitutive binding of Ino2p/Ino4p to UAS INO [13,14], inositol suppresses transcriptional activation via Opi1p, which mediates repression through its activator interaction domain, by binding to the repressor interaction domain of Ino2p [15].…”
Section: Introductionmentioning
confidence: 99%